CONCORDE: VERKRY 'N HOUVAS OP PERSONEEL - M. Broekman (Scientia Militaria, 2012)
As part of the South African Defence Force's manpower information system, Project Concorde was initiated about two years ago. Its aim has been to gain a fuller perspective of manpower utilisation with the Defence Force by employing scientifically accountable principles. The project incorporates four phases: job analysis, job description, job evaluation and the computerisation of the information evaluation technique, which centres on the decision-making aspect involved in the particular job. The writer comments on the reasons for the selection of this technique, and briefly discusses the initial work which the members of the Project have conducted at Chief of Staff Personnel.